Investigation of Nitrate and Ammonium Removal from Groundwater by Mineral Filters - Mohsen Soleimani; Arash Ansarie; Mohammadali Haj Abassie; Jahangir Abedie (آب و فاضلاب, 2008)
Increasing surface and groundwater pollution by ammonium and nitrate makes it necessary to find solutions with minimal environmental impacts. For this purpose, using abundant and high sorption potential soil minerals offers cost-effective and environmentally sound remediation techniques. In this study, Firoozkouh and Semnan zeolites were used for removal of nitrate and ammonium from laboratory solutions and groundwater (Batch method). Zeolite minerals were modified by using the organic surfactant hexadecyltrimethylammonium. A one to tenth ratio of absorbent to solution was used. Results showed that the Semnan natural zeolite and the Firoozkouh modified zeolite treatements, respectively, had the highest and the lowest ammonium sorption levels. The Firoozkouh modified zeolite had the highest nitrate sorption while Semnan natural zeolite had the lowest ammonium sorption. The highest sorption level for ammonium was found to be 0.96 meq g-1 for the Semnan natural zeolite treatment at a concentration of 10 meql-1 and pH=5.5 while the highest sorption for nitrate was found to be 0.8 meq g-1 for the Firoozkouh modified zeolite. Isotherms of nitrate and ammonium sorption levels by natural and modified zeolites showed to match with those of the linear and Fraundlich models.